Chlorophyllum Molybdites “Delicious Poisoning Snack” in Patients Diagnosed with Acute Gastroenteritis - Khusairi, Zainul Ikhwan Ahmad; Fazali, Rizz; WM, Chung; Anuar, Azmir; Ghazali, Afendi (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: Since time immemorial, mushrooms have been used as a part of human diet, some of them are very well known for their nutritive and medicinal properties and some are known to cause poisoning to the human body. A number of post ingestion fatalities due to poisonous mushrooms has been reported worldwide. These poisonous mushrooms are often misidentified as edible ones, which accounts for accidental poisoning. Objective: The main objective of this report was to describe the clinical manifestations of mushroom poisoning cases presented at the Emergency Department (ED), Taiping Hospital. Case Presentation: There were two cases presented, who suffered from moderate dehydration due to acute gastroenteritis after taking 'delicious mushrooms', also known as Chlorophyllum Molybdites. This study found that both cases had complaints of abdominal cramping, diarrhoea and vomiting more than twenty times a day. There was no history of numbness or weakness noted, and no chest pain or shortness of breath. On arrival, both cases presented signs of moderate dehydration with coated tongue and normal blood pressure, with slightly increased in temperature (37.30C). Abdomen was soft but discomfort upon palpation and described as bloated. Both cases were resuscitated with 20ml/kg normal saline. Charcoal, antiemetic, proton pump inhibitor and ceftriaxone antibiotic were given at the ED. Both survived and were treated as infectious acute gastroenteritis. Nausea and vomiting were the most common early symptoms of intoxication and should be considered as a medical emergency. Alpha Amanitin levels should be checked where possible if amanita poisoning is suspected. An early diagnosis and immediate treatment are required for a successful outcome. Conclusion: All patients with the history of mushroom ingestion should be admitted. If laboratory detection of toxin is not available, history of mushroom ingestion, clinical manifestation and their trends could define mushroom poisoning. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S17